Efficient production of recombinant human adiponectin in egg white using genome edited chickens - Kim, Young Min; Park, Jin Se; Choi, Hee Jung; Jung, Kyung Min; Lee, Kyung Youn; Shim, Ji Hyeon; Park, Kyung Je; Han, Jae Yong (Frontiers in Nutrition, 2023)
The prevalence of obesity-related metabolic diseases caused by insulin resistance is rapidly increasing worldwide. Adiponectin (ADPN), a hormone derived from adipose tissue, is a potential therapeutic agent for insulin resistance. Chickens are considered efficient bioreactors for recombinant protein production because they secrete large amounts of high-concentration proteins from the oviduct. Additionally, Chickens express high levels of high-molecular-weight (HMW) ADPN, which is considered the active form in the body. Therefore, in this study, a gene-targeted chicken model was produced in which the gene encoding human ADPN was inserted into Ovalbumin (OVA) using the CRISPR/Cas9 system, and the characteristics of the resulting recombinant ADPN protein were evaluated. As a result, human ADPN was expressed in G1 hen oviducts and egg whites of OVA ADPN knock-in (KI) chickens. The concentration of ADPN in egg white ranged from 1.47 mg/ml to 4.59 mg/ml, of which HMW ADPN accounted for ~29% (0.24–1.49 mg/ml). Importantly, egg white-derived ADPN promoted expression of genes related to fatty acid oxidation and activated the 5’-AMP-activated protein kinase (AMPK) signaling pathway in muscle cells. In summary, the OVA gene-targeted chicken bioreactor proved to be an advantageous model for production of human ADPN, and the resulting protein was of sufficient quantity and efficacy for industrial use.